KEGIATAN MEDIA RELATIONS DEPARTEMEN PENDIDIKAN NASIONAL DALAM SOSIALISASI UJIAN AKHIR NASIONAL - Damayanti, Novita; Santoso, Prasetya Yoga (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
A Media relation is the important part of the public relations in Indonesia government department of education. UAN is the sensitive issue that government needs public relations to work with journalist. Press conference, press visit, press gathering, briefing press, and media center are the activities of Media relations in national departemen of education.